Neuroglobin overexpression induced by the 17β‐Estradiol–Estrogen receptor‐α Pathway reduces the sensitivity of MCF‐7 Breast cancer cell to paclitaxel. Issue 8 (16th June 2016) - Fiocchetti, Marco; Cipolletti, Manuela; Leone, Stefano; Ascenzi, Paolo; Marino, Maria
Abstract: Although paclitaxel (Taxol) is an active chemotherapeutic agent for the treatment of breast cancer, not all breast tumors are sensitive to this drug. In particular, there is a wide agreement on the low sensitivity of estrogen receptor (ER) α‐positive breast cancer to paclitaxel treatment. However, the ERα‐based insensitivity to paclitaxel is still elusive. Here, the effect of the E2/ERα‐dependent upregulation of neuroglobin (NGB), an antiapoptotic globin, on the reduced sensitivity of breast cancer cells to paclitaxel‐induced apoptosis has been evaluated in ERα‐containing MCF‐7 cells. The E2 pretreatment enhances the ERα activity and significantly impairs paclitaxel‐induced apoptosis as evaluated by Annexin V assay and PARP‐1 cleavage. NGB displays a pivotal role in the E2/ERα‐induced antiapoptotic pathway to abrogate paclitaxel‐induced cell death in stable NGB‐silenced MCF‐7 cell clones. Moreover, in the absence of the active ERα, paclitaxel significantly reduces the NGB cell content. In conclusion, these results highlight the involvement of ERα activation and of E2/ERα‐dependent NGB upregulation in the insensitivity of MCF‐7 to paclitaxel. These novel findings could have important implications in the development of targeted therapeutics for overcoming paclitaxel insensitivity in ERα‐positive human breast cancer. © 2016 IUBMB Life, 68(8):645–651, 2016